PENGARUH PROFITABILITAS, SOLVABILITAS, DAN OPINI AUDIT TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (TIMELINESS) DENGAN KUALITAS AUDITOR SEBAGAI VARIABEL MODERATING - Thia Margaretha Tarigan (Universitas Musamus,Merauke,Papua, 2017)
This research aims to verify and provide empirical evidences about: the effect of Profitability, Solvability, and Audit Opinion to Timeliness with Auditor Quality as moderating variabel of manufacturing companies in Indonesia Stock Exchange. The population of this research are 138 manufacturing companies in Indonesia Stock Exchange (BEI) since 2010 – 2014. Sample selection of this research use purposive sampling method. The sample of this research are 78 manufacturing companies. Type of data used are secondary data, that collected by documentation. Statistical tool used is logistic regressions analysis. The result of this research concluded that only profitability have positive significant to timeliness while solvability and audit opinion have not significant to timeliness. Auditor quality as moderating variabel has not strengthened the correlation between profitability, and audit opinion to timeliness but not weaknessed the correlation between solvability to timeliness.